2013
DOI: 10.1371/journal.pone.0080021
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Incision versus Standard Incision Total Hip Arthroplasty Regarding Surgical Outcomes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: PurposeIt remains controversial whether mini-incision (MI) benefits patients in total hip arthroplasty (THA). We performed a meta-analysis of randomized controlled trials (RCTs) to assess the effects of MI on surgical and functional outcomes in THA patients.MethodsA systematic electronic literature search (up to May 2013) was conducted to identify RCTs comparing MI with standard incision (SI) THA. The primary outcome measures were surgical and functional outcomes. According to the surgical approach taken, MI T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…In a study by Chang-peng et al [34], the authors showed that compared to standard incision in THA, there is some evidence that mini-incision reduces blood loss. However, there is no clear definition of Bminimally invasive,^and most would agree that soft tissue trauma is determined, not by length of incision but mainly by trauma to muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Chang-peng et al [34], the authors showed that compared to standard incision in THA, there is some evidence that mini-incision reduces blood loss. However, there is no clear definition of Bminimally invasive,^and most would agree that soft tissue trauma is determined, not by length of incision but mainly by trauma to muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of anteriorly based approaches is that they are tissue sparring by avoiding cutting major muscles and reduces the dislocation rate [ 27 31 ]. Surgery with mini-incision technique is thought to reduce the tissue damage even more and promote faster recovery [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assumptions, but also the controversies, with regard to outcome of these procedures are similar in all minimally invasive procedures. In meta-analysis no significant benefits (focused on blood loss, recovery and analgesia consumption) of these minimally invasive techniques were proven [40][41][42][43]. The outcomes of minimally invasive surgery can be excellent but are not necessarily superior to the standard techniques.…”
Section: Discussionmentioning
confidence: 99%